Voxel-Based Statistical Analysis of 3D Immunostained Tissue Imaging - Vandenberghe, Michel E.; Souedet, Nicolas; Hérard, Anne-Sophie; Ayral, Anne-Marie; Letronne, Florent; Balbastre, Yaël; Sadouni, Elmahdi; Hantraye, Philippe; Dhenain, Marc; Frouin, Frédérique; Lambert, Jean-Charles; Delzescaux, Thierry (Frontiers in Neuroscience, 2018)
Recently developed techniques to visualize immunostained tissues in 3D and in large samples have expanded the scope of microscopic investigations at the level of the whole brain. Here, we propose to adapt voxel-wise statistical analysis to 3D high-resolution images of the immunostained rodent brain. The proposed approach was first validated with a simulation dataset with known cluster locations. Then, it was applied to characterize the effect of ADAM30, a gene involved in the metabolism of the amyloid precursor protein, in a mouse model of the Alzheimer's disease. This work introduces voxel-wise analysis of 3D immunostained microscopic brain images and, therefore, opens the door to unprecedented exploratory investigation of pathological markers and cellular alterations.